Energy auditing and energy saving measure of the lighting systems in the UiTM engineering tower blocks / Mohd Fared Mohd Ali Ambran. - Mohd Aliambran, Mohd Fared (2009)
The lighting systems consume 12% amount of energy supplied in a commercial building in Malaysia16. In UiTM Shah Alam, most of the fluorescent lamps are always turned on 24 hours per day especially at the corridor site which contribute to significant energy wastage. Some areas also use excessive number of fluorescent lamps which the space becomes too bright and this will also contribute energy wastage. Various electrical energy saving measures are reviewed and proposed to be implemented to reduce energy wastage. There are two proposed methods which may reduce the electrical energy wastage from the lighting system. First is by calculating the optimum number of fluorescent lamps which fulfil the minimum requirement of lighting in the area or building. Second is by using a system that can control the lighting system while maintaining a comfort and safe environment in the building. This paper presents a study on the lighting system which focuses on fluorescent lamps at Science and Technology Mara Towers in UiTM Shah Alam especially along the lecturer's room corridor where the most of power wastage occurs. ECS time-based control system is the proposed system that can control the lighting system in the focused area which is expected to contribute a significant reduction in electrical energy consumption in the building is also presented.